Effectiveness of Integrated Skills Approach in Improving English Language Proficiency in Community Schools in Lamjung - Neupane, Binod (English Language Teaching Perspectives, 2024)
Various approaches and methods have been practised to facilitate learners in learning English as a second or foreign language in Nepal. The contemporary approaches to EFL/EFL have replaced the traditional language pedagogy focused on segregating language skills and implemented an integrated approach to language teaching. These pedagogical paradigms underline learning English interconnecting language skills and forms within authentic contexts. This study aims to examine the effectiveness of the integrated approach in improving secondary-level students’ English language proficiency in rural community schools in Lamjung district. Following a quasi-experimental research design guided by the post-positivist paradigm, I experimented with the effectiveness of the integrated approach with secondary-level students studying in Ninth Grade at a community school. The purposively selected students were divided into the experimental group and the control group, having 20 students in each group. After the intervention for a month, the average mean scores achieved by the students in the pre-test and the post-test were analysed statistically. The findings showed the effectiveness of the integrated approach in improving secondary-level students’ English language proficiency in community schools in Nepal. The experimental group performed better in all language skills than the control group. Similarly, students were satisfied with learning English through the integrated approach. The findings can have implications for reshaping the ELT pedagogy following the integrated skills approach at the secondary level.